Adhesive Compositions and Articles

The adhesive composition, with a high elastomer content and polar functional groups, addresses the need for high heat resistance in automotive adhesives, ensuring strong bonding and flexibility in high-temperature environments.

JP7612836B2Active Publication Date: 2025-01-14DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023511373
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-29
Publication Date
2025-01-14
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

Automotive adhesives require high heat resistance to withstand high-temperature treatments during manufacturing and maintain adhesive strength in engine compartments.

Method used

An adhesive composition containing a polymerizable monomer with a carbon-carbon double bond, an elastomer, and a polymerization initiator, with a glass transition temperature of 70°C or higher, featuring a high content of elastomer and polar functional groups for improved heat resistance and stretchability.

Benefits of technology

The adhesive composition demonstrates excellent heat resistance, maintaining adhesive strength and flexibility under high temperatures, effectively bonding lightweight materials in automotive applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612836000001
    Figure 0007612836000001
  • Figure 0007612836000002
    Figure 0007612836000002
  • Figure 0007612836000003
    Figure 0007612836000003
Patent Text Reader

Abstract

An adhesive composition which comprises one or more polymerizable monomers each having a carbon-carbon double bond, an elastomer, and a polymerization initiator. At least some of the polymerizable monomers is a highly polar monomer having a polar functional group and a carbon-carbon double bond. The content of the elastomer is 30 parts by mass or more per 100 parts by mass of the polymerizable monomers. A cured object obtained by curing the adhesive composition at 23°C for 24 hours has a glass transition temperature, as obtained by a dynamic viscoelasticity measurement, of 70°C or higher.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition and an article, more specifically to an adhesive composition and an article comprising a cured product of the adhesive composition. [Background technology]

[0002] Automobile manufacturers are studying ways to reduce the weight of their vehicles in order to reduce carbon dioxide emissions. As part of these studies, they are considering bonding various lightweight materials other than steel with adhesives.

[0003] Adhesives intended for application in automobile manufacturing include, for example, those described in the following Patent Documents 1 and 2.

[0004] Patent Document 1 describes a composition containing the following (A) to (D), which is intended for use as an adhesive in the manufacture of automobiles. (A) a urethane (meth)acrylate having a number average molecular weight of 5,000 or more, in an amount of 40 to 75 parts by mass per 100 parts by mass of the total of (A) and (B); (B) a (meth)acrylic compound containing (B-1) a (meth)acrylate having no urethane bond and (B-2) 15 to 25 parts by mass of (meth)acrylic acid per 100 parts by mass of the total of (A) and (B). (C) Polymerization initiator (D) Reducing agent

[0005] Patent Document 2 describes a two-component adhesive consisting of a first part containing a free radical initiator and a second part containing a reducing agent. This two-component adhesive contains a first monomer which is methyl methacrylate and a second monomer selected from the group consisting of methacrylic acid, a polyfunctional (meth)acrylic acid adduct of an aromatic polyol or a derivative thereof, and a combination thereof. The overlap shear strength of the cured product of this two-component adhesive is 20 MPa or more at 25°C and 7 MPa or more at 120°C, the adhesive strength in a T-peel test at 25°C is 2 kN / m or more, and the glass transition temperature is 130°C or more. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2020 / 100832 [Patent Document 2] JP 2016-155892 A Summary of the Invention [Problem to be solved by the invention]

[0007] In the manufacture of automobiles, high-temperature treatments such as heat treatment in a drying oven are usually carried out after electrodeposition coating, and therefore adhesives used in the manufacture of automobiles are required to have heat resistance. Furthermore, when an adhesive is used in a location exposed to high temperatures, such as an engine compartment, the adhesive naturally requires high heat resistance.

[0008] The present inventors have now carried out investigations with the aim of providing an adhesive composition which has good heat resistance and is preferably used in the manufacture of automobiles. [Means for solving the problem]

[0009] The present inventors have completed the invention provided below and have solved the above problems.

[0010] According to the present invention, a polymerizable monomer having a carbon-carbon double bond; An elastomer; An adhesive composition comprising a polymerization initiator, At least a part of the polymerizable monomers is a highly polar monomer having a polar functional group and a carbon-carbon double bond, The content of the elastomer is 30 parts by mass or more based on 100 parts by mass of the polymerizable monomer, The adhesive composition is cured at 23° C. for 24 hours, and the cured product is subjected to dynamic viscoelasticity measurement to obtain a glass transition temperature of 70° C. or higher. is provided.

[0011] Further, according to the present invention, An article comprising the cured product of the adhesive composition. is provided. Effect of the Invention

[0012] According to the present invention, there is provided an adhesive composition which has good heat resistance and is preferably used, for example, in the manufacture of automobiles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present invention will be described in detail.

[0014] In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5% by mass" means "from 1% by mass to 5% by mass". In the present specification, when the adhesive is a two-part type consisting of a first part and a second part, the amount of each component used preferably represents the amount relative to the total amount of the first part and the second part. In the description of groups (atomic groups) in this specification, when a description is made without specifying whether the group is substituted or unsubstituted, the description includes both groups having no substituents and groups having a substituent. For example, an "alkyl group" includes not only an alkyl group having no substituents (unsubstituted alkyl group) but also an alkyl group having a substituent (substituted alkyl group). In this specification, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate." In this specification, the term "organic group" means an atomic group obtained by removing one or more hydrogen atoms from an organic compound, unless otherwise specified. For example, a "monovalent organic group" refers to an atomic group obtained by removing one hydrogen atom from any organic compound.

[0015] <Adhesive composition> The adhesive composition of the present embodiment contains a polymerizable monomer having a carbon-carbon double bond, an elastomer, and a polymerization initiator. The polymerizable monomer having a carbon-carbon double bond is preferably a polymerizable monomer having a carbon-carbon double bond. At least a part of the polymerizable monomer having a carbon-carbon double bond is a highly polar monomer having a polar functional group and a carbon-carbon double bond. In the adhesive composition of this embodiment, the content of the elastomer is 30 parts by mass or more based on 100 parts by mass of the polymerizable monomer. Furthermore, the adhesive composition of this embodiment is cured at 23°C for 24 hours, and the cured product obtained by measuring the dynamic viscoelasticity has a glass transition temperature of 70°C or higher, preferably 70°C or higher and 220°C or lower, and more preferably 140°C or higher and 220°C or lower.

[0016] The adhesive composition of the present embodiment is believed to strongly interact with the substrate due to the polarity of the polar functional group in the highly polar monomer, which is presumably what leads to good heat resistance, for example, suppression of peeling even after a heat cycle test. In addition, since the adhesive composition of the present embodiment contains a relatively large amount of elastomer, it is believed that excessive curing is suppressed even when exposed to high temperatures, and "ease of stretching" is maintained. By maintaining ease of stretching, stress caused by heating or cooling is easily alleviated, and the heat resistance of the cured adhesive is improved. Furthermore, the adhesive composition of this embodiment is cured at 23°C for 24 hours, and the cured product obtained has a glass transition temperature of 70°C or higher as determined by dynamic viscoelasticity measurement. In other words, the relatively high glass transition temperature of the cured product is also thought to contribute to the good heat resistance.

[0017] The method for producing the adhesive composition of this embodiment will be described in detail below, but will be briefly described here. In producing the adhesive composition of this embodiment, in order to improve performance and various physical properties, it is preferable to appropriately adjust the mixing order and mixing method of each component, rather than simply mixing the components described below. For example, as shown in the examples below, it is preferable to first mix the elastomer and a part of the polymerizable monomer sufficiently uniformly to form a mixture, and then add other components to the mixture and stir it. In this way, it is believed that undesirable separation of the elastomer and the polymerizable monomer is suppressed, and an adhesive composition with better properties can be produced. Furthermore, in order to ensure that the glass transition temperature, as determined by dynamic viscoelasticity measurement of the cured product obtained by curing the adhesive composition of this embodiment at 23°C for 24 hours, is 70°C or higher, it is preferable to use an appropriate amount of a monomer containing a cyclic hydrocarbon skeleton, for example, as explained in general formula (I) described below.

[0018] The components that can be contained in the adhesive composition of the present embodiment and the physical properties of the adhesive composition of the present embodiment will be further described below.

[0019] (Polymerizable monomers having carbon-carbon double bonds) The adhesive composition of the present embodiment contains a polymerizable monomer having a carbon-carbon double bond, preferably a polymerizable monomer having a polymerizable carbon-carbon double bond. A preferred example of the polymerizable carbon-carbon double bond is a polymerizable carbon-carbon double bond possessed by a (meth)acryloyl group. In other words, the polymerizable monomer preferably has a (meth)acryloyl group. At least a part of the polymerizable monomer is a polymerizable monomer having a polar functional group and a carbon-carbon double bond (highly polar monomer). In addition, the polymerizable monomer preferably contains other monomers such as monofunctional monomers and polyfunctional monomers described later. Each monomer will be described below.

[0020] Polymerizable monomers having polar functional groups and carbon-carbon double bonds (highly polar monomers) The adhesive composition of the present embodiment contains a polymerizable monomer having a polar functional group and a carbon-carbon double bond. In this specification, this polymerizable monomer is also referred to as a "highly polar monomer." The highly polar monomer may be monofunctional (having only one polymerizable carbon-carbon double bond) or polyfunctional (having multiple polymerizable carbon-carbon double bonds), but is preferably the former from the viewpoint of the ease of interaction of the polar group with the adherend.

[0021] The polar functional group of the highly polar monomer is preferably a carboxy group, a hydroxy group, or a phosphate group, more preferably a carboxy group or a phosphate group, and even more preferably a carboxy group, from the viewpoint of interaction with components used in automobile manufacturing.

[0022] The polymerizable monomer preferably contains, as a highly polar monomer, at least one selected from the group consisting of (meth)acrylic acid, (meth)acrylic anhydride, fumaric acid, maleic acid, fumaric anhydride, maleic anhydride, and dimers and trimers thereof. Other examples of highly polar monomers include compounds having a phosphoric acid group and a (meth)acryloyl group, and hydroxyalkyl (meth)acrylates.

[0023] Polymerizable monomers with only one carbon-carbon double bond (monofunctional monomers) The adhesive composition of the present embodiment preferably contains, as the polymerizable monomer, a polymerizable monomer having only one carbon-carbon double bond (monofunctional monomer). In this specification, monofunctional monomers having a polar group are classified as the above-mentioned highly polar monomers.

[0024] The polymerizable monomer preferably contains, as a monofunctional monomer, a monomer represented by the following general formula (I). CH2=CHR 1 -COO-R 2 (I) In general formula (I), R 1 is a hydrogen atom or a methyl group, R2 R is a group containing a cyclic hydrocarbon skeleton, and is preferably a group containing a polycyclic hydrocarbon skeleton. 2 The cyclic hydrocarbon skeleton contained in is preferably an alicyclic skeleton containing no aromatic ring.

[0025] Examples of the monomer represented by the general formula (I) include dicyclopentenyloxyethyl (meth)acrylate, norbornene (meth)acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, cyclohexyl (meth)acrylate, etc. Among them, dicyclopentanyl (meth)acrylate is preferable. By including a monomer containing a cyclic hydrocarbon skeleton in the polymerizable monomer, it is easy to design the glass transition temperature of the cured product of the adhesive composition to be 70°C or higher.

[0026] Also, the monofunctional monomer may be a linear or branched alkyl (meth)acrylate.Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate.

[0027] Polymerizable monomers with two or more carbon-carbon double bonds (multifunctional monomers) The adhesive composition of the present embodiment preferably contains, as the polymerizable monomer, a polymerizable monomer having two or more carbon-carbon double bonds (polyfunctional monomer). From the viewpoint of good elongation after curing, the polyfunctional monomer is typically difunctional to hexafunctional, preferably difunctional to tetrafunctional, more preferably difunctional to trifunctional, and further preferably difunctional. In this specification, polyfunctional monomers having a polar group are classified as the above-mentioned highly polar monomers.

[0028] Examples of the polyfunctional monomer include polyfunctional (meth)acrylates having an alicyclic structure, such as dimethylol-tricyclodecane di(meth)acrylate and dimethylol-cyclohexane di(meth)acrylate; polyfunctional (meth)acrylates having an aromatic ring structure, such as ethylene oxide-added bisphenol A di(meth)acrylate (EO-modified BPA di(meth)acrylate), ethylene oxide-added bisphenol F di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate and propylene oxide-added bisphenol F di(meth)acrylate; and polyfunctional (meth)acrylates having an aliphatic branched structure, such as trimethylolpropane tri(meth)acrylate.

[0029] The amount of the polymerizable monomer is, for example, from 40% by mass to 80% by mass, and preferably from 50% by mass to 70% by mass, based on the total non-volatile components of the adhesive composition. When multiple types of polymerizable monomers are used in combination, the ratio of each polymerizable monomer when the total amount of polymerizable monomers is 100 parts by mass is as follows. By appropriately adjusting the ratio, it may be possible to further improve the curability and the elongation of the cured product. Highly polar monomer: preferably from 10 parts by mass to 40 parts by mass, more preferably from 15 parts by mass to 30 parts by mass Monofunctional monomer: preferably from 10 parts by mass to 50 parts by mass, more preferably from 20 parts by mass to 40 parts by mass Polyfunctional monomer: preferably 5 parts by mass or more and 30 parts by mass or less, more preferably 5 parts by mass or more and 20 parts by mass or less

[0030] In addition, the ratio of the monomer represented by formula (I) (containing a cyclic hydrocarbon skeleton) in the total amount of the monofunctional monomer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. In the total amount of the monofunctional monomer, the ratio of the monomer represented by formula (I) (containing a cyclic hydrocarbon skeleton) is preferably 100% by mass or less.

[0031] Incidentally, from the viewpoint of better adhesion to the adherend and maintaining adhesive strength at high temperatures, the amount of polar functional groups contained in the highly polar monomer in the entire adhesive composition is preferably 0.002 mol / g or more, more preferably 0.002 mol / g or more and 0.05 mol / g or less, and even more preferably 0.0025 mol / g or more and 0.04 mol / g or less.

[0032] (Elastomer) The adhesive composition of the present embodiment contains an elastomer.

[0033] The elastomer preferably has a soft segment unit. Specifically, the soft segment unit is at least one selected from the group consisting of a diene structure, an ethylene structure, a propylene structure, an isoprene structure, a urethane structure, an ethylene glycol structure, a propylene glycol structure, a silicone structure, and a chloroprene structure. Among these, a diene structure such as a butadiene structure is preferred. The elastomer may have a hard segment in addition to the soft segment unit. The "soft segment" refers to a flexible portion exhibiting rubber elasticity. The "hard segment" refers to a molecular restraint portion that serves as a crosslinking point of the crosslinked rubber to prevent plastic deformation.

[0034] The content of the soft segment unit in the elastomer is preferably 15% by mass or more and 50% by mass or less, and more preferably 25% by mass or more and 50% by mass or less, of the entire adhesive composition.

[0035] The elastomer preferably contains at least one selected from the group consisting of methyl (meth)acrylate-butadiene-styrene rubber and methyl (meth)acrylate-butadiene-(meth)acrylonitrile-styrene rubber. Furthermore, examples of the elastomer include (meth)acrylonitrile butadiene rubber. The elastomer may also include a urethane oligomer.

[0036] The adhesive composition of the present embodiment may contain only one elastomer, or may contain two or more elastomers. For example, at least one selected from the group consisting of the above-mentioned methyl (meth)acrylate-butadiene-styrene rubber and methyl (meth)acrylate-butadiene-(meth)acrylonitrile-styrene rubber may be used in combination with (meth)acrylonitrile-butadiene rubber. When used in combination, the ratio of the two elastomers in mass ratio is, for example, 1:9 to 9:1, preferably 2:8 to 8:2. The amount of the elastomer is 30 parts by mass or more, preferably 30 parts by mass or more and 60 parts by mass or less, and more preferably 35 parts by mass or more and 45 parts by mass or less, based on 100 parts by mass of the polymerizable monomer.

[0037] (Polymerization initiator) The adhesive composition of the present embodiment contains a polymerization initiator, which polymerizes the carbon-carbon double bonds of the polymerizable monomer, thereby enabling adhesion of articles.

[0038] The polymerization initiator is preferably a thermal radical polymerization initiator. The thermal radical polymerization initiator is preferably an organic peroxide. The organic peroxide may be cumene hydroperoxide, paramenthane hydroperoxide, tertiary butyl hydroperoxide, diisopropylbenzene dihydroperoxide, methyl ethyl ketone peroxide, or tertiary butyl peroxybenzoate. Among these, cumene hydroperoxide is preferred from the viewpoint of stability. By using a polymerization initiator in combination with a reducing agent, which will be described later, it is possible to further increase the curability and achieve room temperature curing.

[0039] The amount of the polymerization initiator is preferably 0.1 parts by mass or more and 20 parts by mass or less, more preferably 0.4 parts by mass or more and 10 parts by mass or less, based on 100 parts by mass of the polymerizable monomer. By using a moderately large amount of the polymerization initiator, the curing speed can be sufficiently increased. On the other hand, by not using too much of the polymerization initiator, sufficient storage stability can be obtained.

[0040] (reducing agent) The adhesive composition of the present embodiment preferably contains one or more reducing agents. By using a polymerization initiator and a reducing agent in combination, it is possible to further increase the curability and achieve room temperature curing. In other words, by using a polymerization initiator and a reducing agent in combination, it is easy to make the glass transition temperature of the cured product obtained by curing the adhesive composition "at 23°C" for 24 hours 70°C or higher. The reducing agent may be any known reducing agent that reacts with the polymerization initiator to generate radicals. The reducing agent is preferably at least one selected from the group consisting of tertiary amines, thiourea derivatives, and transition metal salts, and more preferably transition metal salts. Examples of the transition metal salts include cobalt naphthenate, copper naphthenate, and vanadyl acetylacetonate. Among the transition metal salts, vanadyl acetylacetonate is preferred.

[0041] When a reducing agent is used, the amount used is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the polymerizable monomer. By using 0.01 part by mass or more, the curing speed becomes sufficiently fast, and by using 10 parts by mass or less, the storage stability becomes good.

[0042] (paraffin) The adhesive composition of the present embodiment may contain paraffin. Specifically, various paraffins can be used to accelerate hardening of the part exposed to air. Examples of paraffins include paraffin wax, microcrystalline wax, carnauba wax, beeswax, lanolin, spermaceti, ceresin, and candelilla wax.

[0043] When the adhesive composition of the present embodiment contains paraffin, it may contain only one paraffin, or it may contain two or more paraffins. When the adhesive composition of the present embodiment contains paraffin, the amount is preferably 0.01 parts by mass or more and 3 parts by mass or less, more preferably 0.5 parts by mass or more and 2 parts by mass or less, relative to 100 parts by mass of the polymerizable monomer. By using a relatively large amount of paraffin, the effect of accelerating curing can be sufficiently obtained. On the other hand, by not using too much paraffin, the effect of accelerating curing can be obtained while obtaining sufficient adhesion.

[0044] (Other ingredients) The curable composition of the present embodiment may or may not contain optional components other than those described above. As an example, the curable composition of the present embodiment may contain spacers (particles) for adjusting the film thickness during use. The spacers are typically spherical particles made of a resin such as polyolefin.

[0045] As another example, the adhesive composition of the present embodiment may contain various stabilizers to improve storage stability (suppress deterioration during storage). Examples of stabilizers include (i) compounds known as phenolic antioxidants, such as 2,2'-methylenebis(4-methyl-6-t-butylphenol), (ii) quinone compounds, such as p-benzoquinone and hydroquinone monomethyl ether, (iii) compounds known as polymerization inhibitors, such as amine-based polymerization inhibitors such as phenothiazine, citric acid, and (iv) stable radical-type compounds having stable radicals. Among these, it is desirable to use a stable radical-type compound in terms of improving storage stability without impairing the performance as an adhesive (tensile shear adhesive strength and storage modulus).

[0046] As the stable radical compound, nitroxide radical is preferable. Specific examples of the stable radical compound include 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl. When using a stable radical compound, it is preferable to use one or more of these.

[0047] When a stable radical type compound is used as a stabilizer, the content of the stable radical type compound is, for example, 0.001 part by mass or more and 1 part by mass or less, preferably 0.001 part by mass or more and 0.5 part by mass or less, more preferably 0.01 part by mass or more and 0.3 part by mass or less, and even more preferably 0.02 part by mass or more and 0.1 part by mass or less, relative to 100 parts by mass of polymerizable monomer, in order to improve storage stability without impairing performance as an adhesive.

[0048] When a stabilizer such as a stable radical type compound is used, the content of the stabilizer, particularly the content of a stabilizer other than a stable radical type compound, is, from the viewpoint of improving storage stability without impairing performance as an adhesive, for example, from 0.001 part by mass to 1 part by mass, preferably from 0.001 part by mass to 0.5 part by mass, more preferably from 0.01 part by mass to 0.3 part by mass, and even more preferably from 0.02 part by mass to 0.1 part by mass, relative to 100 parts by mass of polymerizable monomer.

[0049] (One-drug / two-drug) The adhesive composition of the present embodiment may be a so-called one-component type, or a two-component type (two components filled in separate containers that are mixed immediately before use). In the case of the two-part type, the polymerization initiator is preferably contained in the first part and the reducing agent is preferably contained in the second part, but the tertiary amine is preferably contained in the first part, and the thiourea derivative or transition metal salt is preferably contained in the second part. Incidentally, when the adhesive composition of the present embodiment is a two-part type, it is preferable to adjust the amount of each component in the first and second parts so that the adhesive composition after mixing the first and second parts contains each component in the preferred content range described above. Furthermore, the various properties of the adhesive composition described in this specification relate to the adhesive composition after mixing the first and second parts.

[0050] (Characteristics of adhesive composition) The performance of the adhesive composition can be improved not only by adjusting the components of the adhesive composition, but also by adjusting the properties of the adhesive composition, which can be adjusted by appropriately selecting the above-mentioned materials and by employing an appropriate manufacturing method described below.

[0051] The adhesive composition of this embodiment is cured at 23°C for 24 hours, and the breaking elongation of a 1BA type dumbbell test piece described in Appendix A of JIS K 7161-2, measured at a tensile speed of 10 mm / min in accordance with JIS K 7162, is preferably 30% or more, more preferably 40% or more and 100% or less at 23°C, and is preferably 30% or more, more preferably 40% or more and 100% or less at 80°C. A moderately large breaking elongation of the cured product of the adhesive composition is considered to mean that the cured product of the adhesive composition effectively relieves stress generated in heat cycle tests, etc. In particular, in the automotive field, where different types of components with different thermal expansion coefficients are often bonded to each other, a moderately large breaking elongation of the cured product of the adhesive composition is considered to provide effective stress relief. Furthermore, the fact that the breaking elongation at 23°C (near room temperature) is appropriately large and that the breaking elongation at 80°C is relatively large indicates that the adhesive composition of this embodiment is preferably used in the manufacture of automobiles.

[0052] A test piece obtained by using the adhesive composition of this embodiment under the following [Preparation Conditions] is subjected to a tensile shear adhesion test at 23°C and a tensile speed of 10 mm / min. The tensile shear adhesion strength is represented by F 23 In addition, a test piece obtained by using the adhesive composition of this embodiment under the following [Preparation Conditions] is subjected to a tensile shear adhesion test at 120° C. and a tensile speed of 10 mm / min, and the tensile shear adhesive strength is represented by F 120 In this case, F 120 is preferably 8 MPa or more, more preferably 10 MPa or more and 30 MPa or less, and further preferably 12 MPa or more and 30 MPa or less. 120 / F 23 is preferably 0.5 or more, more preferably 0.6 or more and 1 or less, and further preferably 0.7 or more and 1 or less.

[0053] By designing an adhesive composition so that the adhesive strength is 8 MPa or more at the high temperature of 120°C, it is believed that peeling at high temperatures, which is expected when applied to the automotive field, can be suppressed. Also, F120 / F 23 It is believed that, for example, the results of a heat cycle test can be improved by designing an adhesive composition so that the difference in adhesive strength between near room temperature and at high temperatures is relatively small, i.e., the difference is 0.5 or more.

[0054] The adhesive composition of the present embodiment was cured at 23° C. for 24 hours to obtain a cured product. The storage modulus at 80° C. was measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, in a measurement temperature range of 0° C. to 250° C., at a heating rate of 5° C. / min in a tensile mode. The storage modulus was E' at 80° C. 80 Then, E' 80 is preferably 100 MPa or more, more preferably 150 MPa or more and 500 MPa or less, and further preferably 200 MPa or more and 500 MPa or less. The adhesive composition of the present embodiment was cured at 23° C. for 24 hours to obtain a cured product. The storage modulus at 23° C. was measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, in a measurement temperature range of 0° C. to 250° C., at a heating rate of 5° C. / min in a tensile mode. The storage modulus at 23° C. was E' 23 The storage modulus at 80°C is E' 80 In this case, E' 80 / E' 23 is preferably 0.2 or more, more preferably 0.3 or more and 1 or less, and further preferably 0.4 or more and 1 or less. E' 80 is 100 MPa or more, and / or E' 80 / E' 23 It is believed that by designing an adhesive composition so that the storage modulus of the cured product is 0.2 or more, that is, so that the storage modulus of the cured product is appropriately large even at high temperatures, softening of the cured product that may lead to a decrease in adhesive strength even at high temperatures can be suppressed, and it is believed that the results of, for example, a heat cycle test can be improved.

[0055] The adhesive composition of this embodiment is cured at 23°C for 24 hours, and the cured product is measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, a measurement temperature range of 0°C to 250°C, a heating rate of 5°C / min, and in a tensile mode to obtain a loss tangent (tan δ)-temperature curve. The peak top temperature of this temperature curve is preferably 100°C or higher and 220°C or lower, more preferably 140°C or higher and 220°C or lower. The full width at half maximum of this temperature curve is preferably 40°C or higher and 120°C or lower, more preferably 50°C or higher and 100°C or lower. The full width at half maximum refers to the distance between the positions on both sides of the maximum value that indicate half the value of the maximum value.

[0056] Roughly speaking, tan δ is an index that represents the "tenacity" of the object being measured. The fact that the peak top temperature of the tan δ graph is 140°C or more and 220°C or less, and the full width at half maximum is 50°C or more and 100°C or less, can be interpreted as meaning that the cured product of the adhesive composition of this embodiment has various "tenacities" in the temperature range expected for automotive applications and can be preferably used for bonding different types of materials.

[0057] The viscosity of the adhesive composition of this embodiment may be appropriately set depending on the coatability and the like. For example, the viscosity of the adhesive composition measured using a Brookfield viscometer (rotor No. 7) at 25° C. and a rotation speed of 20 rpm or 2 rpm is typically 50,000 mPa·s or more and 100,000 mPa·s or less.

[0058] <Items / Applications, etc.> By applying the adhesive composition of the present embodiment to an article and curing it, an article including a cured product of the adhesive composition can be obtained. The adhesive composition of the present embodiment can be cured (at room temperature) without heating and can bond articles (particularly when it contains a polymerization initiator and a reducing agent). Of course, heating is not excluded when bonding articles.

[0059] As already mentioned, the adhesive composition of the present embodiment is preferably used in the manufacture of automobiles from the viewpoint of excellent heat resistance, etc. Furthermore, automobile manufacturers are considering bonding various lightweight materials other than iron (non-ferrous metals, reinforced resins, etc.) with adhesives, and the adhesive composition of the present embodiment is also preferably applied to bonding these materials.

[0060] In this specification, an "adhesive composition" has been described that contains a polymerizable monomer having a carbon-carbon double bond, an elastomer, and a polymerization initiator, and specifies the content of the elastomer and the glass transition temperature of the cured product. However, the adhesive composition described in this specification can also be used in fields other than adhesion, such as a coating material or an injection agent. In other words, the adhesive composition described in this specification can also be used as a composition with no limited use, a curable composition, or a resin composition.

[0061] <Method of manufacturing adhesive composition> In producing the adhesive composition of the present embodiment, it is preferable to appropriately adjust the mixing order, mixing method, etc. of the components, rather than simply mixing the above-mentioned components. In the production of the adhesive composition, it is particularly preferable that the elastomer and the polymerizable monomer are mixed thoroughly. For this reason, as shown in the examples below, it is preferable to (i) first mix at least a part of the elastomer and at least a part of the polymerizable monomer thoroughly and uniformly at 50 to 80°C to obtain a mixture, and (ii) then add other components to the mixture and stir it. By doing so, it is considered that the elastomer and the polymerizable monomer are thoroughly and uniformly mixed. The adhesive composition produced in this way tends to easily satisfy, for example, the properties of the adhesive composition described above (elongation at break, tensile shear adhesive strength, storage modulus, loss tangent, etc.) compared to adhesive compositions obtained by other production methods.

[0062] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. EXAMPLES

[0063] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.

[0064] <Raw materials> The raw materials shown in Table 1 below were prepared.

[0065] [Table 1]

[0066] <Production of Adhesive Composition> [Example 1 Agent A (First Agent)] The mixture was prepared in a temperature-controllable container equipped with a stirrer according to the following procedure. The amounts of each ingredient added were as shown in Table 2 below.

[0067] (1) Weighing and preparation After putting FA-513M, CIT, and P-56 into the container, the temperature was raised to 70℃. It was confirmed that the CIT had dissolved and the internal temperature was between 60℃ and 70℃. N250SL was then added. Dissolution and dispersion was then carried out for 1 hour. It was then visually confirmed that there was no residual P-56 or CIT remaining. (2) Weighing and preparation The mixture obtained in (1) above was cooled, and Miramer M2101 and AM were added at 50°C or less. BL-20 was added in two portions at 40°C or less. The mixture was then stirred overnight at an internal temperature of 30°C. It was then visually confirmed that there were no aggregates of BL-20 or undissolved N250SL. (3) Weighing and preparation 1300X33VTBNX LC was added to the mixture obtained in (2) above, and then the mixture was stirred and dispersed for 2 hours. The internal temperature during this was set to 30° C. It was then confirmed that there was no unevenness in the mixture. (4) Vacuum defoaming The mixture obtained in (3) above was subjected to a defoaming treatment under the conditions of 0.08 MPa / 30 minutes. (5) Weighing and preparation In-D and PBQ were added to the mixture after the treatment in (4) above, and the mixture was stirred for 30 minutes. The internal temperature was 30° C. It was then confirmed that there was no unevenness in the mixture. (6) Weighing and preparation PH-80 was added to the mixture obtained in (5) above, and the mixture was stirred for 30 minutes or more. The internal temperature during this was set to 30° C. It was then confirmed that there was no unevenness in the mixture. (7) Vacuum defoaming The mixture obtained in (6) above was subjected to a defoaming treatment under the conditions of 0.08 MPa / 10 minutes.

[0068] The viscosity of the mixture after the treatment in (7) above was measured at 25°C and 20 rpm using a Brookfield viscometer (rotor No. 7). The viscosity was within the range of 50,000 mPa s to 100,000 mPa s. The resulting mixture was then passed through a 40 mesh filter. In this manner, Example 1 Agent A was obtained.

[0069] [Example 1 Agent B (Second Agent)] The mixture was prepared in a temperature-controllable container equipped with a stirrer according to the following procedure. The amounts of each ingredient added were as shown in Table 2 below. (1) Weighing and preparation After putting FA-513M, CIT, and P-56 into the container, the temperature was raised to 70℃. After confirming that CIT had dissolved and the internal temperature was between 60℃ and 70℃, N250SL was added. Dissolution and dispersion were carried out for 1 hour. It was then visually confirmed that no P-56 or CIT remained undissolved. (2) Weighing and preparation The mixture obtained in (1) above was cooled, and Miramer M2101 and AM were added at 50°C or less. BL-20 was added in two portions at 40°C or less. The mixture was then stirred overnight at an internal temperature of 30°C. It was then visually confirmed that there were no aggregates of BL-20 or undissolved N250SL. (3) Weighing and preparation 1300X33VTBNX was added to the mixture obtained in (2) above, and then the mixture was stirred and dispersed for 2 hours. The internal temperature during this was set to 30° C. It was then confirmed that there was no unevenness in the mixture. (4) Vacuum defoaming The mixture obtained in (3) above was subjected to a defoaming treatment under the conditions of 0.08 MPa / 30 minutes. (5) Weighing and preparation After adding SIPOMER PAM 4000 to the mixture after the treatment in (4) above, the mixture was stirred for 30 minutes or more. The internal temperature was kept at 30°C. (6) Weighing and preparation PSN and In-M were added to the mixture obtained in (5) above, and then the mixture was stirred for 30 minutes or more. The internal temperature during this was set to 30° C. It was then confirmed that there was no unevenness in the mixture. (7) Weighing and preparation After adding VO(AA)2 to the mixture obtained in (6) above, the mixture was stirred for 30 minutes or more. The internal temperature was set to 30° C. It was then confirmed that there was no unevenness in the mixture. (8) Vacuum defoaming The mixture obtained in (7) above was subjected to a defoaming treatment under the condition of 0.08 MPa / 10 minutes.

[0070] The viscosity of the mixture after the treatment in (8) above was measured at 25°C and 20 rpm using a Brookfield viscometer (rotor No. 7). The viscosity was within the range of 50,000 mPa s to 100,000 mPa s. The resulting mixture was then passed through a 40 mesh filter. In this manner, Example 1 formulation B was obtained.

[0071] [Table 2]

[0072] [Example 2 and onwards] The adhesive compositions of Examples 2 and onward were also produced in the same manner as in Example 1, except that the raw materials used and their amounts were partially changed, by first mixing the elastomer and the polymerizable monomer thoroughly and uniformly, and then adding the other components and, if necessary, performing a degassing treatment or the like. The compositions of the adhesive compositions in Examples 2 and onwards are as shown in Table 3 below. The adhesive compositions in Examples 2 and onwards were also produced in the same way as in Example 1, as a two-part type consisting of an A agent (first part) and a B agent (second part). In this case, the amounts of each material in A agent and B agent were either equal to each other as in Example 1, or added only to A agent or only to B agent. However, the table shows the composition after the two parts are mixed. Note that the components used and their amounts other than the elastomer, polymerizable monomer and stable radical compound are not specified, as they are the same as in Example 1.

[0073] Among the components listed in Table 3 below, information regarding some of the components not listed in Table 1 and some listed in Table 1 is provided below in additional detail. BL-20: Soft segment unit content 46% by mass Urethane oligomer: Arkema CN9004, polyether-type bifunctional aliphatic urethane acrylate, soft segment unit content 88% by mass 1300X33VTBNX LC: Methacrylate-functional butadiene-acrylonitrile liquid rubber, soft segment unit content 82% by weight N250SL: Soft segment unit content 81% by mass DCPD type methacrylate: dicyclopentanyl methacrylate EO BPA dimethacrylate: Miramer M2101, structure as follows

[0074] [ka]

[0075] Methacrylic acid: polar functional group content 0.012 mol / g Hydroxypropyl methacrylate: polar functional group content 0.007 mol / g SIPOMER PAM 4000: Phosphate ester of 2-hydroxyethyl methacrylate, polar functional group content 0.006 mol / g

[0076] <Measurement and Evaluation> Each of the following measurements and evaluations was performed three times, and the average of the three values ​​obtained was used as the result.

[0077] [Dynamic viscoelasticity measurement] First, a cured product (test piece) of the adhesive composition was prepared for measuring dynamic viscoelasticity. Specifically, the test piece was prepared as follows (1) to (3). (1) First, a 0.5 mm thick silicone sheet with a 5 x 40 mm hole was placed on a PET film. The curable composition was applied to the hole to form a coating film. (2) Another PET film was laminated on top of the coating film. Then, both sides were sandwiched between 1 cm thick glass plates, and a weight was placed on top to press the film. In this state, the film was aged for 24 hours in a room at a temperature of 23°C and a relative humidity of 50 RH%. The pressure was then released and the PET film was peeled off. In this way, a sheet-like cured product was obtained. Incidentally, the film thickness was adjusted to approximately 500 μm depending on the thickness of the silicone sheet. (3) The above sheet-like cured product was cut into rectangular test pieces measuring 0.5×5×40 mm.

[0078] The dynamic viscoelastic properties of the obtained test pieces were measured using a dynamic viscoelasticity measuring device (DMS7100, manufactured by SII) under the conditions of frequency: 1.0 Hz, mode: tensile mode, measurement temperature range: 0°C to 250°C, and heating rate: 5°C / min, and data was obtained. Based on the obtained data, the full width at half maximum of the temperature-loss tangent (tan δ) graph, the peak top temperature of the loss tangent (tan δ) (tan δ peak value, i.e., glass transition temperature), and the storage modulus (E') at 23°C or 80°C were calculated. 23 and E' 80 ) was sought.

[0079] [Tensile shear adhesion test (SPCC-SPCC)] The evaluation was performed in accordance with JIS K 6850. Specifically, the adhesive composition (after mixing the two-component type) was applied to one side of a test piece (25 mm x 100 mm x 1.6 mmt cold-rolled steel plate (SPCC), degreased with acetone) to form a film, and the other test piece (25 mm x 100 mm x 1.6 mmt SPCC) was immediately superimposed on the surface of the film and bonded. Then, the test piece was cured at room temperature (23 ° C.) for 24 hours. In this way, a sample for measuring tensile shear adhesive strength was obtained. Incidentally, the film thickness of the adhesive composition was adjusted to approximately 100 μm (= 0.1 mm) due to the action of the polyethylene filler (spacer for adjusting the film thickness) contained in the composition. Using the above sample, a tensile shear adhesion test was performed at a tensile speed of 10 mm / min using an Instron universal testing machine Model 5569 under an environment of 23°C and 50% relative humidity, and the tensile shear adhesion strength F 23 was measured. In addition, a similar tensile shear adhesion test was conducted except that the temperature during the tensile shear adhesion test was changed from 23°C to 120°C, and the tensile shear adhesion strength F 120 was measured.

[0080] [Tensile shear adhesion test (CFRP-SPCC)] A sample for measuring tensile shear adhesive strength was obtained in the same manner as in the above [Tensile shear adhesion test (SPCC-SPCC)], except that the test piece to which the adhesive composition was applied was changed from SPCC to a fiber-reinforced plastic, specifically, an epoxy CFRP (25 mm × 100 mm × 2.0 mmt, pretreatment: #320 sanding, then IPA degreasing). The tensile shear adhesion test was performed using an Instron universal testing machine Model 5569 at a temperature of 23°C and a relative humidity of 50% at a tensile speed of 10 mm / min. The tensile shear adhesion strength F 23 ' was measured. In addition, a similar tensile shear adhesion test was conducted except that the temperature during the tensile shear adhesion test was changed from 23°C to 120°C, and the tensile shear adhesion strength F 120' was measured.

[0081] [Heat cycle test] A sample similar to that used in the above [Tensile shear adhesion test (CFRP-SPCC)], i.e. a sample bonded between epoxy CFRP and SPCC, was subjected to a heat cycle test of four cycles, each cycle consisting of "cooling at -40°C for 1.5 hours, then heating at 90°C for 4 hours." As described above in [Tensile shear adhesion test (SPCC-SPCC)], the tensile shear adhesion strength F0 of the sample before the heat cycle test and the tensile shear adhesion strength F1 after the heat cycle test were measured. Then, the change in adhesive strength due to the heat cycle was evaluated by F1 / F0. In the heat cycle test, the temperature increase rate was set to 2°C / min and the temperature decrease rate was set to 2°C / min.

[0082] [Storage stability test] The viscosity of components A and B of the adhesive composition of each Example and Comparative Example immediately after production (initial viscosity of the adhesive) was measured. The viscosity of Agent A was also measured after it was left to stand for 3 days at 60° C. The rate of increase in viscosity of Agent A over time was then calculated. All viscosity measurements were performed using a Brookfield viscometer (rotor No. 7) at 25°C and 20 rpm. [Elongation at break] The test methods were based on JIS K 7161-2 and JIS K 7162. The hardened specimens of 1BA type dumbbell shape described in JIS K 7161-2 Appendix A, which were obtained by curing for 24 hours in an environment of 23°C and relative humidity of 50%, were used and measurements were performed at a tensile speed of 10 mm / min in an atmosphere of 23°C. The tensile tester used was "INSTRON5967" (manufactured by Instron Corporation), and the breaking elongation was measured. For evaluation at high temperatures, samples were cured for 24 hours in an environment of 23°C and 50% relative humidity, then heated in a high temperature bath SPHH-201 (manufactured by Espec Corporation, registered trademark) at 80°C for 30 minutes and then evaluated in the same manner in an 80°C atmosphere.

[0083] Table 3 shows the composition of the adhesive composition (only some of the components) and the measurement and evaluation results. In Table 3, the amount of each component of the adhesive composition is given in parts by mass. In Table 3, the amount of polar functional groups contained in the highly polar monomer in the entire composition was calculated based on the molecular weight and number of polar functional groups of each raw material, the blending ratio in the adhesive, etc., with carboxyl groups, hydroxyl groups, and phosphate groups defined as polar functional groups. In Table 3, the amount of soft segment units in the elastomer in the entire composition was calculated from the content in each raw material and the blending ratio in the adhesive, with the butadiene unit in the MMA-BD-AN-ST copolymer, the butadiene unit in the NBR, and the polyether polyol in the urethane acrylate as soft segments. The correlation between Table 2 and Table 3 is, for example, as follows: In Example 1 of Table 3, the content of BL-20 relative to a total of 100 parts by mass of the first and second agents is 5 parts by mass of agent A in Table 2 + 5 parts by mass of agent B in Table 2 = 10 parts by mass. In Example 1 of Table 3, the content of TEMPO relative to a total of 100 parts by mass of the first and second agents is 0.01 parts by mass of agent A in Table 2 + 0 parts by mass of agent B in Table 2 = 0.01 parts by mass.

[0084] [Table 3]

[0085] The adhesive compositions of Examples 1 to 8 (which have a relatively high elastomer content and a relatively high glass transition temperature of the cured product) have a F 120 , F 120 / F 23 , F' 120 , F' 120 / F' 23 From these values ​​and the results of the heat cycle test, it is understood that the heat resistance is good and that the material is preferably used in the manufacture of automobiles. Moreover, the adhesive compositions of Examples 1 to 8 had good storage stability.

[0086] On the other hand, the adhesive compositions of the Comparative Examples were inferior to the Examples in the following respects, for example. Comparative Example 1: Probably because the amount of elastomer was small, the evaluation result of the elongation at break was worse than that of the Examples, and the results of the heat cycle test were also worse than those of the Examples. Comparative Example 2: Probably because the glass transition temperature of the cured product was designed to be low, F 120 , F 120 / F 23 , F' 120 , F' 120 / F' 23 The values ​​and the like were worse than those of the Examples, and the results of the heat cycle test were also worse than those of the Examples.

[0087] This application claims priority based on Japanese Patent Application No. 2021-059636, filed on March 31, 2021, the disclosure of which is incorporated herein in its entirety.

Claims

1. a polymerizable monomer having a carbon-carbon double bond; An elastomer; An adhesive composition comprising a polymerization initiator, at least a part of the polymerizable monomers is a highly polar monomer having a polar functional group and a carbon-carbon double bond; the polar functional group is a carboxy group, a hydroxy group, or a phosphate group; The content of the elastomer is 30 parts by mass or more based on 100 parts by mass of the polymerizable monomer, the adhesive composition is cured at 23° C. for 24 hours, and the cured product has a glass transition temperature of 70° C. or higher as determined by dynamic viscoelasticity measurement; the adhesive composition is cured at 23°C for 24 hours, and the resulting 1BA dumbbell test piece as described in Appendix A of JIS K 7161-2 has a breaking elongation, measured at a tensile speed of 10 mm / min in accordance with JIS K 7162, of 30% or more at 23°C and 30% or more at 80°C; The adhesive composition was cured at 23° C. for 24 hours, and the resulting cured product was measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, a measurement temperature range of 0° C. to 250° C., a temperature rise rate of 5° C. / min, and in a tensile mode. The storage modulus at 80° C. was defined as E′ 80 . An adhesive composition having an E' 80 of 100 MPa or more.

2. The adhesive composition according to claim 1, The adhesive composition was cured at 23° C. for 24 hours, and the resulting cured product was measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, a measurement temperature range of 0° C. to 250° C., a temperature rise rate of 5° C. / min, and in a tensile mode. The storage modulus at 23° C. was E′ 23 and the storage modulus at 80° C. is E′ 80 When E' 80 / E' 23 The adhesive composition according to claim 1, wherein

3. a polymerizable monomer having a carbon-carbon double bond; An elastomer; An adhesive composition comprising a polymerization initiator, at least a part of the polymerizable monomers is a highly polar monomer having a polar functional group and a carbon-carbon double bond; the polar functional group is a carboxy group, a hydroxy group, or a phosphate group; The content of the elastomer is 30 parts by mass or more based on 100 parts by mass of the polymerizable monomer, the adhesive composition is cured at 23° C. for 24 hours, and the cured product has a glass transition temperature of 70° C. or higher as determined by dynamic viscoelasticity measurement; the adhesive composition is cured at 23°C for 24 hours, and the resulting 1BA dumbbell test piece as described in Appendix A of JIS K 7161-2 has a breaking elongation, measured at a tensile speed of 10 mm / min in accordance with JIS K 7162, of 30% or more at 23°C and 30% or more at 80°C; The adhesive composition was cured at 23°C for 24 hours, and the resulting cured product was measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, a measurement temperature range of 0°C to 250°C, a temperature rise rate of 5°C / min, and in a tensile mode. When the storage modulus at 23°C was E'23 and the storage modulus at 80°C was E'80, An adhesive composition having an E' 80 / E' 23 of 0.2 or more.

4. The adhesive composition according to any one of claims 1 to 3, The test piece obtained under the following [Preparation Conditions] is subjected to a tensile shear adhesion test at 23° C. and a tensile speed of 10 mm / min. The tensile shear adhesion strength is F 23 year, The test piece obtained under the following [Preparation Conditions] is subjected to a tensile shear adhesion test at 120° C. and a tensile speed of 10 mm / min. The tensile shear adhesion strength is F 120 When F 120 is 8 MPa or more, F 120 / F 23 The adhesive composition according to claim 1, wherein [Creation conditions] (1) The adhesive composition is applied to one side of a cold-rolled steel plate to form a film having a thickness of 0.1 mm. (2) Another cold-rolled steel plate is placed on the surface of the film, and the film is hardened at room temperature for 24 hours to obtain a test specimen.

5. The adhesive composition according to any one of claims 1 to 4, The adhesive composition was cured at 23°C for 24 hours, and the cured product was measured using a dynamic viscoelasticity measuring device at a frequency of 1 Hz, a measurement temperature range of 0°C to 250°C, a heating rate of 5°C / min, and in a tensile mode. In the loss tangent (tan δ)-temperature curve, The peak top temperature of the temperature curve is 140° C. or higher; The adhesive composition, wherein the full width at half maximum of the temperature curve is 50°C or more and 100°C or less.

6. The adhesive composition according to any one of claims 1 to 5, The adhesive composition, wherein the elastomer has a soft segment unit.

7. The adhesive composition according to claim 6, The adhesive composition, wherein the soft segment unit is at least one selected from the group consisting of a diene structure, an ethylene structure, a propylene structure, an isoprene structure, a urethane structure, an ethylene glycol structure, a propylene glycol structure, a silicone structure, and a chloroprene structure.

8. The adhesive composition according to claim 6 or 7, The adhesive composition, wherein the content of the soft segment unit in the elastomer is 15 mass % or more and 50 mass % or less based on the entire adhesive composition.

9. The adhesive composition according to any one of claims 1 to 8, The adhesive composition, wherein the elastomer comprises at least one selected from the group consisting of methyl (meth)acrylate-butadiene-styrene rubber and methyl (meth)acrylate-butadiene-(meth)acrylonitrile-styrene rubber.

10. The adhesive composition according to any one of claims 1 to 9, An adhesive composition, wherein the content of the polar functional group in the entire adhesive composition is 0.002 mol / g or more.

11. The adhesive composition according to any one of claims 1 to 10, The adhesive composition, wherein the polar functional group comprises a carboxy group.

12. The adhesive composition according to any one of claims 1 to 11, The adhesive composition, wherein the polymerizable monomer comprises at least one selected from the group consisting of (meth)acrylic acid, (meth)acrylic anhydride, fumaric acid, maleic acid, fumaric anhydride, maleic anhydride, and dimers and trimers thereof.

13. The adhesive composition according to any one of claims 1 to 12, The adhesive composition, wherein the polymerizable monomer comprises a monomer represented by the following general formula (I): CH 2 =CHR 1 -COO-R 2 (I) In general formula (I), R 1 is a hydrogen atom or a methyl group, R 2 is a group containing a cyclic hydrocarbon skeleton.

14. 14. The adhesive composition according to claim 13, R 2 is a group containing a polycyclic hydrocarbon skeleton.

15. The adhesive composition according to any one of claims 1 to 14, The adhesive composition further comprises a stable radical type compound having a stable radical.

16. 16. The adhesive composition of claim 15, The adhesive composition, wherein the stable radical is a nitroxide radical.

17. 17. The adhesive composition according to claim 15 or 16, The adhesive composition wherein the stable radical type compound comprises at least one selected from the group consisting of 1-oxyl-2,2,6,6-tetramethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl, and 4-methacryloyloxy-2,2,6,6-tetramethylpiperidine 1-oxyl.

18. The adhesive composition according to any one of claims 15 to 17, The adhesive composition has a stable radical compound content of 0.001 parts by mass or more and 0.5 parts by mass or less based on 100 parts by mass of the polymerizable monomer.

19. The adhesive composition according to any one of claims 1 to 18, The adhesive composition further comprises a reducing agent.

20. 20. The adhesive composition of claim 19, The adhesive composition is a two-part adhesive composition that is composed of a first part and a second part and is mixed together immediately before use, An adhesive composition, wherein the first agent contains the polymerization initiator, and the second agent contains the reducing agent.

21. An article comprising a cured product of the adhesive composition according to any one of claims 1 to 20.

Citation Information

Patent Citations

  • Adhesive resin composition

    JP2012102224A

  • Active energy ray-curing type adhesive composition

    JP2013112715A

  • Two-part adhesive

    JP2016155892A

  • Curable composition

    JP2020033395A

  • Adhesive composition, circuit connecting material, connecting structure for circuit member, and semiconductor device

    WO2005121266A1